Bayesian inference for risk assessment of the position of study program within the integrated university: a case study of engineering management at technical faculty in Bor - Savic, Marija; Djordjevic, Predrag; Nikolic, Djordje; Mihajlovic, Ivan; Zivkovic, Zivan (Serbian Journal of Management, 2014)
This paper defines issues involved with the Integrated University (IU) from the aspect of the positioning of study program (SP) as the basic component of modern IU. Model for the risk assesment of the SP position in IU is developed on the principles of Bayes’ theorem of conditional probability. In the proposed model, a priori probability is updated with previous events (evidence nodes) ei, whose occurrence caused a final posterior probability of the position of SP in IU. Defined model was developed based on the example of SP - Engineering management (EM) within the Technical Faculty in Bor, in order to assess the probability of its position in the future IU in Belgrade. The results show that SP-EM has a probability above 99% with its current structure and new activities, to be a part of the IUB. Defined model has a universal character and can be applied to analyze the posterior probability of any SP’s position and risk assesment with the variation of the number and content of the evidence nodes ei.